2004
DOI: 10.1143/jjap.43.4786
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Filter on Actuator for System Stability of 9.5 mm Drive

Abstract: We propose a redesign method for modal parameters to depress the second resonance peak of an ultraslim optical pickup actuator. With the addition of the countermode near the second resonance frequency, we can achieve the gain margin, which is sufficient to meet the system requirement. It would alleviate the burden of the additional filter for a high-speed drive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Adding for the comparison, the data transfer rate of BD 1x is defined as 36 Mbps and the one of DVD 1x is defined as 1.38 Mbps. To achieve high rotational speed of disc with maintaining the system stability, pickup actuator should have high resonance frequencies and low resonance peaks of flexible modes (Song et al 2001(Song et al , 2004Lee et al 2002). The frequencies are depend on the structural stiffness of the moving part of the actuator.…”
Section: Introductionmentioning
confidence: 99%
“…Adding for the comparison, the data transfer rate of BD 1x is defined as 36 Mbps and the one of DVD 1x is defined as 1.38 Mbps. To achieve high rotational speed of disc with maintaining the system stability, pickup actuator should have high resonance frequencies and low resonance peaks of flexible modes (Song et al 2001(Song et al , 2004Lee et al 2002). The frequencies are depend on the structural stiffness of the moving part of the actuator.…”
Section: Introductionmentioning
confidence: 99%
“…An optical pickup actuator is a core component in optical storage devices and used to write the information or read it by positioning precisely an objective lens (OL) on the disk as a track following device. To realize above-mentioned requirements, it is essential for the optical pickup actuator to have wide servo bandwidth and high sensitivity (Lee et al 2002;Song et al 2004;Lee et al 2005b). This servo bandwidth is controlled by flexible mode frequencies and flexible mode peaks which are caused by the flexibility of moving parts in the actuator.…”
Section: Introductionmentioning
confidence: 99%
“…To settle them as the index of the performance of actuators, the gain margin is defined as the absolute value of the difference between the gain at 1 kHz and the gain at the first flexible mode frequency. If an actuator did not have sufficient gain margins, total system becomes unstable for high-speed operations in high density reading and recording (Song et al 2001;Lee et al 2002;Song et al 2004). Therefore, the flexible mode frequencies and peaks of optical pickup actuators are the most important factors for high density reading and recording.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to write and read the information by positioning precisely an objective lens (OL) on the disk as a track following device. To realize above-mentioned requirements, it is essential for the optical pickup actuator to have high sensitivity, wide servo bandwidth, and small size (Lee et al 2002(Lee et al , 2005cSong et al 2004). But, to use existing methods to increase the data capacity such as BD and HD-DVD, a very precise focusing servo system and flat disk substrate are needed because the working distance and the defocus margin of OL are relatively small and so a pickup actuator can collide with disk media.…”
Section: Introductionmentioning
confidence: 99%
“…van der Aa et al (2002) reported the realization for a small form factor optical (SFFO) drive, featuring 1 GB on a 30 mm rewritable optical disk, using the linear actuator of rack and pinion type and the four-wire spring type actuator, with dimensions comparable to PCMCIA-like drives. Song et al (2004) introduced a method of improving the gain margin by the redesign of modal parameters for an ultraslim COMBO actuator. Ke and Huang (2004) designed a novel slim tilt-controllable actuator having a printed circuit board as its lens holder for optical pickup heads through DOE procedures.…”
Section: Introductionmentioning
confidence: 99%